SPATIOTEMPORAL CHARACTERISTICS OF EXTREME RAINFALL EVENTS OVER JAVA ISLAND, INDONESIA Case: East Java Province - , SUPARI, Prof. Dr. HA. Sudibyakto M.S ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Extreme rainfall event is one of natural events frequently generating serious impact to many sectors. To date, its characteristic is expected being changing due global climate change. The study was aimed to identify the spatio- temporal characteristics of extreme rainfall events over Java Island, Indonesia by focusing analysis to East Java Province. Some extreme indices calculated as annual series, were generated from rainfall record within period of 1981 â 2010. The maximum number of consecutive wet days, number of days where daily rainfall is more than or equal to 20 mm, 50 mm and 90 th percentile were chosen to represent the frequency of extreme rainfall events. Meanwhile the highest 1-day rainfall amount, the highest 5-day rainfall amount, annual total and daily rainfall intensity were selected to represent the intensity of the events. A set of quality control procedures including duplicated data check, spatial outliers check, missing value check and homogeneity test was applied prior the analysis. The spatial characteristic of those events was identified by mapping climatological mean of indices while temporal characteristic was assessed using the non-parametric Mann-Kendal test. The quality control procedures selected 84 stations as high quality data from total of 461 rainfall stations. The spatial pattern of extreme rainfall events over East Java Province is generally characterized by low frequency and intensity in the coastal area, and high frequency and intensity in the mountainous area. The dominant finding from trend assessment is not-significant trend. However, the consistently significant trend was observed in some districts. Rain stations in District of Ponorogo, Ngawi, Bojonegoro, Gresik and Sumenep showed significant negative trend for almost all indices whereas significant positive trend was found in District of Surabaya and Pasuruan.